Macrobiotus sklodowskae sp. nov. (Tardigrada: Eutardigrada: Macrobiotidae, richtersi group) from Cyprus - Michalczyk, Łukasz; Kaczmarek, Łukasz; Węglarska, Barbara (Zootaxa, 2006)
A new species, Macrobiotus sklodowskae sp. nov. is described from moss samples collected in Cyprus. The new species belongs to the richtersi group and differs from the most similar M. gerlachae Pilato et al., 2004 mainly by having a bigger microplacoid with lateral wings and lacking a small cap-like structure on top of the egg processes.